Evaluation of Automobile Engine Oil Alternatives with FUCOM, MAIRCA, MABAC and BWM Methods - Volkan Genç; Aşkın Özdağoğlu; Murat Kemal Keleş (Journal of Transportation and Logistics)
Engine oils used in automobiles have an impact on many factors such as fuel consumption, wear that will occur with the effect of friction in the parts of the engine, efficiency and performance of the engine. Therefore, choosing a quality engine oil is important in terms of increasing the performance of the car’s engine, using it efficiently and prolonging its life. The aim of this study is to determine the most optimal one among the 5w30 engine oil alternatives for private cars offered by leading brands in the automotive industry in Turkey. For this purpose, eight criteria have been determined by technical people who are experts in their fields. The weights of the criteria were found by considering two different climatic conditions, namely İzmir with a warm climate and Erzurum with a continental climate, using the new weighting methods BWM and FUCOM. The five engine oil alternatives were listed according to the criteria weights found for İzmir and Erzurum by MABAC and MAIRCA methods. In the light of the analysis, the “viscosity 100” criterion was the first for İzmir, the “cold starting simulator” criterion was the first for Erzurum. The last criterion for both İzmir and Erzurum is the “Viscosity index” criterion. In the evaluation of engine oils made by MAIRCA and MABAC methods according to the climate conditions of Izmir and Erzurum, the order of engine oil alternatives for Izmir and Erzurum was the same. In the last pahse the results were compared and suggestions were made.